Characteristics of microcontact printing with polyelectrolyte ink for the precise preparation of patches on silica particles. Issue 69 (23rd November 2018) - Zimmermann, Marc; Grigoriev, Dmitry; Puretskiy, Nikolay; Böker, Alexander
Abstract : A detailed analysis of microcontact printing on different sized silica particles using polyelectrolyte ink is presented including controlled patch geometries. Abstract : This publication demonstrates the abilities of a precise and straightforward microcontact printing approach for the preparation of patchy silica particles. In a broad particle size range, it is possible to finely tune the number and parameters of three-dimensional patches like diameter and thickness using only polyethyleneimine ink, poly(dimethoxysilane) as stamp material and a suitable release solvent.